Pengaruh Pesan Dakwah Terhadap Kesadaran Toleransi Umat Beragama - Larasati, Naura Fatha; Sarbini, Ahmad; Sukayat, Tata (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The aim of this study is to examine the religious messages conveyed by the podcast "Berbeda Tapi Bersama," the forms of religious tolerance, and how the messages in this podcast influence awareness of tolerance. This research employs a quantitative method with simple regression analysis and an objective approach aimed at developing causal theories. The sample consists of 70 KPI (Islamic Communication and Broadcasting) students, determined using the Slovin formula and random sampling technique for data collection. The theory applied is the S-O-R (Stimulus-Organism-Response) theory, which suggests that stimuli can influence individuals to change their attitudes. The results of the study indicate that the religious messages in the podcast "Berbeda Tapi Bersama" have an influence on the tolerance awareness of KPI students, accounting for 44.8% of the variance in the religious message variable.